New methods in diagnosis and therapySuccessful treatment of a young woman with acute complicated myocardial infarction - Serpytis, Pranas; Smigelskaite, Akvile; Kibarskis, Aleksandras; Katkus, Rimgaudas; Samalavicius, Robertas; Glaveskaite, Sigita; Rackauskas, Gediminas (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2013)
Therapeutic hypothermia is method used to improve the neurological status of patients who are at risk of ischaemia after myocardial infarction. We report a case of a 28-year-old woman who suffered acute myocardial infarction complicated by ventricular fibrillation. The patient was successfully resuscitated. Invasive and non-invasive medical treatment was applied including therapeutic hypothermia. Success was achieved due to adequate public reaction, fast transportation, blood vessel revascularization and application of therapeutic hypothermia. The patient was successfully discharged after one week of treatment, and just minor changes in heart function were present.